Performance of CDMA power control for HAPS - S Abdulwafi, Tahani Almehdi (2015)
In parallel with terrestrial and satellite wireless networks, a new alternative based on platforms located in the stratosphere has recently introduced, known as High Altitude Platforms (HAPS). HAPS are either airships or aircraft positioned between 17 and 22.5 km above the earth surface. It has capability to deliver a wide spectrum of applications to both mobile and fixed users over a broad coverage area. Wideband code division multiple access (WCDMA) has emerged as the mainstream air interface solution for 3G networks. Also the ITU has specifically authorized the use of some IMT-2000 (3G) frequency bands from HAPS. This project addresses downlink and uplink power control for high altitude platform station for a WCDMA under the assumption of power control imperfections. However in real systems power control imperfections degrade the system capacity. In this project, the performance of two distance based forward link power control schemes (nth-power-of distance and optimum power control schemes) are evaluated for high altitude platform station (HAPS) W-CDMA systems. For a HAPs system with 37 beams, the total capacity of the system would be in the order of 1776 voice users or 233 data users. The coverage of the platform with 37 beams each with a radius of 1.2 km can by approximated by a circle with a radius of 8 km.For uplink case the system capacity would be 2627 voice user and 370 data user. Thus, for the voice and data service, the uplink capacity is higher than the downlink capacity.